Membrane trophic effect of hyperglycemia on the anterior chamber angle tissues in ocular hypertension (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Although there is a significant progress in the treatment of diabetic ocular complications, the issue of prevention and therapy for this pathology is still unstudied. The purpose of the present study was to study the stability of lysosomal membranes in the anterior chamber angle tissues in ocular hypertension under hyperglycemia conditions.Materials and Methods. A total of 32 male chinchilla rabbits, weight 2.5-3.2 kg, were involved into the experiment.The experimental animals were divided into 4 groups: group I, 8 rabbits served as control; group II, 8 rabbits with DB under ocular hypertension conditions (DM+OH group); group III, 8 rabbits with DM (DM-only group); group IV, 8 rabbits with ocular hypertension (OH-only group). Each group was subdivided into 2 subgroups depending on the time point of the follow up: subgroup i, 3 weeks; subgroup ii, 6 weeks. Activity of free and bound forms of acid phosphatase (ACP) in the anterior chamber angle tissues was determined.Results. Data obtained revealed that ocular hypertension development in streptozotocin-induced diabetic rats caused significant decrease in stability of lysosomal membrane in intracellular structure of tissues studied.Conclusions. It was established that under the conditions of ocular hypertension, streptozotocin-induced diabetic animals had a marked failure in the stability of anterior chamber angle tissue lysosomes. In such conditions, the activity of free marker enzyme increased by more than 40% and the level of bound marker enzyme decreased by 47.7%. Whereas, these indices were equal to 26.1% and 25.3%, respectively, when ocular hypertension was simulated in normoglycemic rabbits. Thus, we can conclude that hyperglycemia has a negative effect on the intracellular ultra structures of the anterior chamber angle tissues in the development of ocular hypertension.
Keywords: ocular hypertension; diabetes; anterior chamber angle tissue; acid phosphatase